Estimation of genetic parameters for the tick and hemoparasite burden in Angus cattle - David, Gabriela [UNESP]; da Silva Arce, Cherlynn Daniela [UNESP]; de Araujo Neto, Francisco Ribeiro; de Albuquerque, Lúcia Galvão [UNESP]; Giglioti, Rodrigo; Okino, Cíntia Hiromi; de Almeida Regitano, Luciana Correia; de Sena Oliveira, Márcia Cristina; de Oliveira, Henrique Nunes [UNESP] (Springer Nature, 2023)
The study was conducted with the objective of estimating genetic and phenotypic parameters for tick (CRM) and Babesia bigemina (IBBi), Babesia bovis (IBBo), and Anaplasma marginale (IAM) burden in Angus female breed in Brazil. The sample group was composed of Angus females raised in herds located in a region of endemic instability for cattle tick fever in the state of Rio Grande Sul (RS), Brazil. The variance components were estimated using Bayesian inference and Gibbs sampling algorithm, considering a multi-trait animal model. Heritability estimates showed values of low magnitude, ranging from 0.03 (IBBo) to 0.16 (CRM), while repeatability estimates ranged between 0.07 (IBBo) and 0.21 (CRM). Regarding the genetic correlation estimates, the values showed low (−0.01 for IBBo × IAM) to moderate (0.55 between IBBi × IAM) magnitudes. The results indicate that it is possible to use tick count and hemoparasite infection levels as selection criteria, with small genetic gains.
Keywords: Animal breeding; Gibbs samples; Quantitative genetics; Resistance